Pembangunan Dashboard Produksi Pada PTPN XII Persero Kantor Wilayah III Gunung Gambir Berbasis Web - Sofyan Syahri Huzaini; Bayu Priyambadha; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PTPN XII Gunung Gambir is a state-owned corporation that active in plantation industry located in Jember. Now Gunung Gambir manage tea and latex comodities. Everyday the outcome of production report by manual use Handy Talky and to make the report still use Microsoft Excel. The reportation of the outcome data is reported between one place to another place that usually encounter unfitted data because of the miss heard of information from the sender. The data that have sent is repeated by manual from prior report have recaped in microsoft excel. It can causes problems such as the not acurate and not simple and then the process will take long time. The recapotulation of production report by Microsoft Excel also difficult to read, to analyze, and to predict the data because most of information that shown in the form of numbers. To solve that problems we make production6 dashboard system based on web that it will be expected to simplify the sending process of data then to simplify the monitoring all the production process by simple and interesting appearance. So it can help to determine the next strategy. This research start from analyzing process of the requirement system by interview and observation directly in Gunung Gambir. The next step is planning that can be divide to architectur planning, component planning, data planning anf interface planning. The next step is implementation that relize the system that built before. Both steps are done by object oriented approach. The next step is unit testing, integration testing, and validation testing.